The adaptability of Ulmus pumila and the sensitivity of Populus sibirica to semi-arid steppe is reflected in the stem and root vascular cambium and anatomical wood traits - Dimitrova, Anastazija; Balzano, Angela; Tsedensodnom, Enkhchimeg; Byambadorj, Ser-Oddamba; Nyam-Osor, Batkhuu; Scippa, Gabriella Stefania; Merela, Maks; Chiatante, Donato; Montagnoli, Antonio (Frontiers in Plant Science, 2024)
Afforestation success is measured by the tree establishment and growth capacity which contribute to a range of ecosystem services. In the Mongolian steppe, Populus sibirica and Ulmus pumila have been tested as candidate species for large afforestation programs, by analyzing their response to a combination of irrigation and fertilization treatments. While in temperate and Mediterranean forest ecosystems, xylogenetic studies provide insight into the trees’ plasticity and adaptability, this type of knowledge is non-existent in semi-arid regions, whose climatic features are expected to become a global issue. Furthermore, in general, a comparison between the stem and root response is scarce or absent. In the present study, we show that the anatomical traits of the vascular cambium and the xylem, from stem and root microcores, reflect the previously noted dependence of P. sibirica from irrigation – as they proportionally increase and the higher adaptability of U. pumila to drought – due to the reduced impact across all five characteristics. As the first wood anatomy study of these species in semiarid areas, future research is urgently needed, as it could be a tool for quicker understanding of species’ suitability under expected to be exacerbated semi-arid conditions.